As dimensões da ação supervisora do supervisor de ensino do município de Santos: limites e perspectivas - Santos, Elise Cordeiro (2016)
This study focuses on the supervisory actions of tenured School Supervisors, at the Municipal School System in Santos, SP, with the purpose of establishing meaning to effectively developed actions in their working context. Technical and supervisory identity, suggested by historical analysis of the job position, shows influences on the career path that, from the political and social variants of the contemporary educational context, enables the perception of a renewed attitude of the supervisory action, aligned with the training, normative and pedagogical dimensions. The guiding research questions depict the profile and career path of Santos School Supervisors and problematize the supervisory action, in its possibilities, challenges and perspectives. The theoretical framework has been based on the following authors: Saviani (2002); Silva Jr (1986); Gadotti (1989); Martha Nogueira (1989); Paulo Freire (1997); Naura S. Ferreira (2002) Nilda Alves (2011); Mary Rangel (2011), among others. As regards to research methods, apart from a documentary search, we supplemented data of historical nature with accounts from retired, tenured Supervisors from the Municipal School System. In the current group of supervisors, we applied a questionnaire in order to set a profile of this group as well as identifying priorities and challenges of the supervisory action. A number of supervisors contributed to form a discussion group, in order to explore issues that emerged from the questionnaire and thus, extracting indicators that show improvement in the supervisory action. Data was analyzed from the perspective of content analysis. In the results, positive characteristics have identified systemic vision, leadership and the performance of this group in the educational process. Challenges for the job were reported as flaws in the training program and in communication, and the difficulty in political positioning in the face of educational policies. We also identified indicators of productivity from the perspective of normative, training and teaching dimensions, with emphasis on professional growth of School Supervisors in Santos, before the needs that were diagnosed during the mediation of the educational process of this city.